Deconstructing Dinosaurs : The History of the German Tendaguru Expedition and its finds, 1906-2023 - Heumann, Ina; Stoecker, Holger; Vennen, Mareike (Life Sciences E-Book Collection, 2025., 2024)
Deconstructing Dinosaurs takes a fresh look at the history of the German Tendaguru Expedition (1909-1913), using recently uncovered sources to reveal how Berlin's Natural History Museum appropriated and extracted 225 tonnes of dinosaur fossils from land belonging to modern-day Tanzania. It examines the colonial conditions under which the area's inhabitants located, excavated, and prepared the finds and carried them out of the country's interior to the coast. Once in Berlin, the fossils were transformed into valuable scientific assets and prize exhibits, foremost among them Giraffatitan brancai . This specimen, a prominent subject of provenance and restitution debates, is used to explore the colonial legacy of natural history collections and the social and political responsibilities of the museums that hold them.